Impaired coronary blood flow at higher heart rates during atrial fibrillation: Investigation via multiscale modelling. (July 2019) - Scarsoglio, S.; Gallo, C.; Saglietto, A.; Ridolfi, L.; Anselmino, M.
Highlights: We computationally study the role of atrial fibrillation (AF) on coronary perfusion. Different heart rates (HR=50, 70, 90, 110, 130 bpm) in AF are explored. Coronary hemodynamics is altered due to the HR increase and beat-to-beat variability. Higher HR during AF exerts a coronary blood flow impairment. Imbalanced myocardial oxygen supply-demand ratio is found for HR>90–110 bpm in AF. Abstract: Background: Different mechanisms have been proposed to relate atrial fibrillation (AF) and coronary flow impairment, even in absence of relevant coronary artery disease (CAD). However, the underlying hemodynamics remains unclear. Aim of the present work is to computationally explore whether and to what extent ventricular rate during AF affects the coronary perfusion. Methods: AF is simulated at different ventricular rates (50, 70, 90, 110, 130 bpm) through a 0D-1D multiscale validated model, which combines the left heart-arterial tree together with the coronary circulation. Artificially-built RR stochastic extraction mimics the in vivo beating features. All the hemodynamic parameters computed are based on the left anterior descending (LAD) artery and account for the waveform, amplitude and perfusion of the coronary blood flow. Results: Alterations of the coronary hemodynamics are found to be associated either to the heart rate increase, which strongly modifies waveform and amplitude of the LAD flow rate, and to the beat-to-beat variability. The latter is overall amplified in the coronary circulation as HR grows, even though the input RR variability is kept constant at all HRs. Conclusions: Higher ventricular rate during AF exerts an overall coronary blood flow impairment and imbalance of the myocardial oxygen supply-demand ratio. The combined increase of heart rate and higher AF-induced hemodynamic variability lead to a coronary perfusion impairment exceeding 90–110 bpm in AF. Moreover, it is found that coronary perfusion pressure (CPP) is no longer a good measure of the myocardial perfusion for HR higher than 90 bpm.